2021
DOI: 10.21203/rs.3.rs-961626/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globulin and Albumin To Globulin Ratio Precisely Diagnose Periprosthetic Joint Infection and Determine The Timing of Second-Stage Reimplantation

Abstract: Background Periprosthetic joint infection (PJI) is one of the most challenging complication of total joint arthroplasty (TJI). An early and accurate diagnosis of PJI is associated with better treatment outcomes. However, whether the platelet-related markers and globulin-related markers can be used to assist the diagnosis of PJI remains elusive. Methods 206 patients underwent revision hip or knee arthroplasty in our institution were divided into two groups: 79 patients in PJI group and 127 patients in aseptic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…1, and the QUADAS‐2 score criteria revealed that most of the extracted studies had high risks. Excluding brand new markers that only appeared recently and have limited data, 129 records reported diagnostic information of serum markers (serum CRP, ESR, procalcitonin, IL‐6, D‐Dimer, WBC, platelet count [PLT], neutrophil to lymphocyte ratio [NLR], monocyte to lymphocyte ratio [MLR], platelet to lymphocyte ratio [PLR], platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), 9–11,24–149 114 studies reported synovial markers (synovial WBC, PMN%, IL‐6, IL‐1β, CRP, TNF‐α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral‐flow based α‐defensin test),…”
Section: Resultsmentioning
confidence: 99%
“…1, and the QUADAS‐2 score criteria revealed that most of the extracted studies had high risks. Excluding brand new markers that only appeared recently and have limited data, 129 records reported diagnostic information of serum markers (serum CRP, ESR, procalcitonin, IL‐6, D‐Dimer, WBC, platelet count [PLT], neutrophil to lymphocyte ratio [NLR], monocyte to lymphocyte ratio [MLR], platelet to lymphocyte ratio [PLR], platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), 9–11,24–149 114 studies reported synovial markers (synovial WBC, PMN%, IL‐6, IL‐1β, CRP, TNF‐α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral‐flow based α‐defensin test),…”
Section: Resultsmentioning
confidence: 99%